PERANCANGAN BRAND ACTIVATION KEBUN STROBERI DESA LEBAKMUNCANG PADA KELUARGA MUDA BERSAMA SUSU ULTRA MILK. - Zainindiyah, Amelia; Syafikarani, Aisyi; Agung Rangga, I Gusti (Telkom University, 2024)
Bandung has highlands which are suitable for gardening such as strawberries.One of the places used as a place for gardening is Lebakmuncang Village. Not only forgardening land but also for tourist attractions that have an agro-educational tourismconcept where visitors can learn to garden guided by farmers. However, it is a shamethat Lebakmuncang Village Strawberry Farm has never carried out a brand activation promotional strategy such as holding existing exhibition events such as the West JavaGarden Fest event. West Java Garden Fest. This research can produce a promotionalstrategy in the form of an exhibition event that is suitable for the tourism potential of Lebakmuncang Village with a target audience of young families who like to spend time with their family on holiday. Keywords: tourism village, strawberries, Lebakmuncang Village, exhibition event.